2017
DOI: 10.1093/ageing/afx124
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol versus placebo for delirium prevention in acutely hospitalised older at risk patients: a multi-centre double-blind randomised controlled clinical trial

Abstract: prophylactic low-dose oral haloperidol did not reduce delirium incidence in acutely hospitalised older patients. Therefore, prophylactic use of haloperidol in this population is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…68 A recent multicentre RCT of medical and surgical patients aged 70 yr compared the antipsychotic drug haloperidol or placebo on top of nonpharmacological strategies to prevent POD. 143 There was no difference in delirium incidence, duration, or severity. Melatonin has shown conflicting results as a preventative agent for POD in a few small RCTs.…”
Section: Preventionmentioning
confidence: 88%
See 1 more Smart Citation
“…68 A recent multicentre RCT of medical and surgical patients aged 70 yr compared the antipsychotic drug haloperidol or placebo on top of nonpharmacological strategies to prevent POD. 143 There was no difference in delirium incidence, duration, or severity. Melatonin has shown conflicting results as a preventative agent for POD in a few small RCTs.…”
Section: Preventionmentioning
confidence: 88%
“…177 Another multicentre RCT published after the meta-analysis found no effect of prophylactic haloperidol on delirium severity or duration. 143 A comparison of typical vs atypical antipsychotics did not find a consistent trend in improvement of symptoms to recommend one over another. 177 Other drugs used in the treatment of delirium include melatonin and cholinesterase inhibitors.…”
Section: Treatmentmentioning
confidence: 94%
“…21 The HARPOON study randomized 245 acutely hospitalized elderly patients to prophylactic haloperidol versus placebo and found no clear differences in delirium incidence, duration, severity, or 3-month mortality. 117 The MIND-USA study compared haloperidol, ziprasidone, and placebo in a randomized, double-blind trial and found no effect of either antipsychotic medication on the number of coma-free and delirium-free days (►Fig. 3).…”
Section: Changing Perspectives On Antipsychoticsmentioning
confidence: 99%
“…Interventions aimed at reducing the incidence and severity of delirium have been studied in various settings, but our preliminary searches revealed a paucity of ED research. 15 Multicomponent prevention programmes in hospitalised patients showed a reduction in delirium incidence. 16 17 Several Cochrane reviews have been published since 2012, which reported the utility of pharmacological agents, 18 19 delirium prevention programmes in hospital setting 16 and long-term care.…”
Section: Introductionmentioning
confidence: 99%